Novel scalable aerosol-assisted CVD route for perovskite solar cells - Ratnasingham,SR; Mohan,L; Daboczi,M; Degousée,T; Binions,R; Fenwick,O; Kim,J-S; McLachlan,MA; Briscoe,J (Materials Advances, 2021)
Organo-metal halide perovskite research has progressed rapidly, with photovoltaic (PV) devices achieving over 25% power conversion efficiency (PCE). However, scalable production of these devices is an ongoing challenge. We demonstrate the growth of methylammonium lead triiodide (MAPI) films via a novel two-step aerosol-assisted chemical vapour deposition (AACVD) method leading to the first ever perovskite-based PV devices using active layers deposited by AACVD. This is a scalable deposition process, requiring less complex equipment than conventional CVD. Furthermore, our method utilises methanol (MeOH) as the only solvent, as opposed to harmful solvents typically used in perovskite processing. Structural and optical characterization confirms successful formation of MAPI with no secondary phases and an optical bandgap of ∼1.58 eV. The final film had large grains (order of μm), with thickness ranging from 500–1100 nm. These films were used to fabricate working PV devices resulting in a champion PCE of 5.4%. While films demonstrated high structural and compositonal quality, we identified large film roughness as a limiting factor in device PCE, and elucidate the origin of this via detailed study of the film growth, which reveals a unique multi-step film formation process.